ショウワキチ デ カンソク サレタ ヘイズ ゲンショウ - 原, 圭一郎; ハラ, ケイイチロウ; 長田, 和雄; オサダ, カズオ; 矢吹, 正教; ヤブキ, マサノリ; 橋田, 元; ハシダ, ゲン; 山内, 恭; ヤマノウチ, タカシ; 林, 政彦; ハヤシ, マサヒコ; et al. (2010)
P(論文) 2004-2007年に行ったエアロゾル重点観測中に,昭和基地でヘイズ現象が観測された.ヘイズ現象時は風が比較的弱く,降雪・地吹雪は観測されず,冬～ 春にヘイズが出現していた.「南極ヘイズ」時には,バックグラウンド状態と比べてエアロゾル数濃度が1-2桁ほど増加していた.エアロゾル成分のバルク分析から,ヘイズ現象中のエアロゾル主成分は海塩成分(e.g., Na^+, Cl^->)と判明した.流跡線解析とNAAPSモデルから,南アメリカやアフリカ南部でのバイオマス燃焼の影響を受けた空気塊が,南大洋上の低気圧活動に伴って昭和基地まで輸送されていることが示唆された.中低緯度域から極域方向への空気塊流入と,輸送中の海塩粒子の発生と混合とにより,「南極ヘイズ」が出現しているのだろう.バックグラウンド時とヘイズ時のO_3 濃度の差は,冬よりも極夜明け後の春に大きくなる傾向が確認された.不均一反応により海塩粒子から高反応性ハロゲン化合物が放出されることがあるため,極夜明け後の南極沿岸域でのヘイズ現象は,地上O_3 消失現象にも密接に関連している可能性がある. During our aerosol measurement program at Syowa Station, Antarctica in 2004-2007, some low visibility (haze) phenomena were observed under conditions with weak wind and without drifting snow and fog in winter-spring. In the "Antarctic haze" phenomenon, the number concentration of aerosol particles and black carbon concentration increased by one-two orders higher relative to background conditions at Syowa Station, while surface O_3 concentration simultaneously dropped especially after polar sunrise. Major aerosol constituents in the haze phenomenon were sea-salts (e.g., Na^+ and Cl^-). From the trajectory analysis and NAAPS model, the plumes from biomass burning in South America and southern Africa were transported to Syowa Station, Antarctic coast, during eastward (occasionally westward) approach of cyclones in the Southern Ocean. Thus, poleward flow of the plume from mid-latitudes and injection of sea-salt particles during the transport may lead to the Antarctic haze phenomenon at Syowa Station. The difference of O_3 concentration between the background and the haze conditions tended to be larger in spring (polar sunrise) relative to that in winter. Because enhancement of sea-salt particles can play an important role as an additional source of reactive halogen species, the haze episodes might make a significant contribution to surface O_3 depletion during the polar sunrise on the Antarctic coast. departmental bulletin paper